SILENT GUT GANGRENE- A SURGICAL RARITY - Dr. Snehasis Smrutiranjan Das, . Vikyath Shetty HP; Dr. Mari raj M; Dr. Gopal Balasubramanian (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Mesenteric Arterial Ischemia is an entity which is one of the most important causes for acute abdomen and resulting laparotomy and bowel resection and the associated morbidity. Definitive diagnosis of the same is done by Contrast enhanced CT although mostly laparotomy is indicated by clinical status of the patient and routine blood investigations with blood gas studies. There is also a recent surge in such cases due to COVID 19 pandemic. We present a 52-year-old male who presented with acute abdomen who was found to have Superior Mesenteric Artery Thrombosis with gangrene of near complete small bowel and ascending colon managed with resection of the same. Extensive bowel resection and the resulting short bowel syndrome and associated morbidities makes Mesenteric Ischemia a time sensitive emergency. Mortality is usually associated with increasing time taken for diagnosing the condition. Hence early diagnosis with prompt surgical treatment is key for patient management